CBMT-45. SEX-SPECIFIC METABOLIC ADAPTIONS IN GLIOBLASTOMA. (11th November 2019) - Sponagel, Jasmin; Zhang, Shanshan; Chinnaiyan, Prakash; Rubin, Joshua; Ippolito, Joseph
Abstract: Glioblastoma (GBM) is the most common and aggressive brain tumor in adults. GBM occurs more commonly in males, but female patients survive significantly longer. Understanding the molecular mechanisms that underlie those sex differences could support novel treatment strategies. In this regard, we found that male and female GBM patient samples differ in their metabolite abundance and that male patients exhibit a significantly higher abundance of TCA cycle metabolites. We confirmed those findings in a murine model of GBM, which has previously yielded important insights into sexual dimorphism in GBM. Strikingly, sex differences in TCA cycle flux were entirely driven by glutamine flux, not glucose flux, suggesting a sex-specific role for glutamine in GBM. Metabolic manipulation through glutamine deprivation resulted in a greater growth inhibition in male GBM cells. Glutamine itself can be utilized for anabolic reactions or it can be converted to glutamate by glutaminase. Only male GBM cells were sensitive to pharmacological glutaminase inhibition with BPTES or CB-839, suggesting that male GBM cells are glutamate dependent while female GBM cells are not. Concordantly, we found significantly higher glutaminase levels in male GBM cells. Furthermore, we found that numerous metabolites (including NADH, ATP, and glutathione) involved in cellular processes downstream of glutamate were more abundant in male GBM cells. In contrast, female GBM cells were resistant to low glutamine conditions and glutaminase inhibitors unless glutamine-synthase activity was disrupted, suggesting that glutamine synthesis might play a more prominent role in female GBM. Together, these data indicate that male and female GBM differ in their metabolic adaptions. Male GBM utilize glutamate to fuel the TCA cycle and mitochondrial activity while female GBM synthesize and utilize glutamine itself. This sexual dimorphism in metabolic reprogramming reveals novel sex specific metabolic targets for GBM and underlines the importance of considering sex in metabolic targeting approaches.